In vitro evaluation of fluoride products in the development of carious lesions in deciduous teeth - Lucineide de Melo Santos; José Ivo Limeira dos Reis; Maria Perolina de Medeiros; Sheyla Moreira Ramos; Juliane Mendes de Araújo (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The purpose of this study was to evaluate the effect of the application of fluoride products on the development of enamel caries in deciduous teeth. A total of 108 deciduous teeth were chosen for the study. Acid-resistant varnish was applied on the teeth, leaving only one area of 5 mm x 1 mm of dental enamel exposed. The teeth were allocated randomly to one of the following groups: 1) control - toothpaste without fluoride; 2) 1.23% fluoride gel; 3) Duraflur fluoride varnish; 4) Duraphat fluoride varnish; 5) Fluorniz fluoride varnish; 6) Fluorphat fluoride varnish; 7) varnish with Duofluorid; 8) 12% silver fluoride diamine (Cariestop); 9) children's fluoride toothpaste (500 ppm). The tested products were applied on the teeth according to the manufacturer's recommendations and the teeth were stored in a moist environment for 24 hours. Each group of teeth was then subjected to a pH cycling model for 14 days, after which the teeth were cut through the center for an analysis of the depth of the carious lesion by polarized light microscopy. Comparisons were made between the treatments and the control group. The mean lesion depth values were 318 μm ± 39 (control), 213 μm ± 27 (fluoride gel), 203 μm ± 34 (Duraflur), 133 μm ± 25 (Duraphat), 207 μm ± 27 (Fluor-niz), 212 μm ± 27 (Fluorphat), 210 ± 28 (Duofluorid), 146 ± 31 (Cariestop) and 228 ± 24 (fluoride toothpaste). None of the products used here was able to completely prevent the formation of lesions. The highest cariostatic effect was achieved by fluoride varnish Duraphat and the lowest by the fluoride toothpaste.